2022
DOI: 10.3389/fcimb.2022.972929
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium subsp. paratuberculosis and Hashimoto’s thyroiditis: Is MAP the trigger?

Abstract: Hashimoto’s thyroiditis (HT) is an autoimmune disorder of the thyroid gland that can cause hypothyroidism. As HT is a multifactorial disorder, activation of immune responses in genetically predisposed individuals exposed to some environmental factors can contribute to it. Microorganisms, as environmental factors, including Mycobacterium avium ssp. paratuberculosis (MAP) by molecular mimicry, can be important in this autoimmune disorder. This study aimed to investigate the association between MAP and HT. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In our previous investigation, we MAP DNA and antibodies in autoimmune disorders like RA (not yet published), and HT in this area [ 51 , 52 ]. These findings indicated that people in this region are repeatedly exposed to MAP, and it emphasizes the importance of the healthcare system being aware of this problem.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous investigation, we MAP DNA and antibodies in autoimmune disorders like RA (not yet published), and HT in this area [ 51 , 52 ]. These findings indicated that people in this region are repeatedly exposed to MAP, and it emphasizes the importance of the healthcare system being aware of this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies [23,[27][28][29][30], we selected four microorganisms, including enterovirus, herpesvirus, Helicobacter pylori, and Yersinia enterocolitica, for the analysis of molecular mimicry between antigens derived from these potentially relevant pathogens and thyroid autoantigens (TPO and Tg). The analysis was conducted in several steps.…”
Section: Epitope Predictionmentioning
confidence: 99%
“…Investigations have also suggested that, bacterial pathogens such as Yersinia enterocolitica, Helicobacter pylori, and Mycobacterium avium ssp. paratuberculosis might be associated with the onset of HT [27][28][29][30]. The current case-control and in-silico study were designed to explore the genetic susceptibility and protective patterns in our HT patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although it remains unclear whether MAP is a potential public health threat [ 20 , 21 , 22 ], visitors to petting zoos and zookeepers should observe safety precautions.…”
Section: Introductionmentioning
confidence: 99%